Formaldehyde in Seafood: A review - Laly, S J; Priya, E. R.; Panda, S. K.; Zynudheen, A. A. (Fishery Technology, 2018)
Seafood is a nutrient rich commodity accepted all over the world. Illegal addition of formalin (37% formaldehyde) to seafood for extending shelf life affects the health of consumers as it is identified as a potential carcinogen by International Agency for Research on Cancer (IARC). The occurrence of naturally varying levels of formaldehyde present in different food materials including seafood due to post-mortem enzymatic reaction makes the monitoring of illegally added formalin difficult. Understanding the natural levels of free formaldehyde along with proper regulation and monitoring of this harmful chemical is essential for safeguarding health of seafood consumers.